2010
DOI: 10.21608/eajbsa.2010.15205
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects of three commercial formulations of Bacillus thuringiensis (Agerin, Dipel 2X and Dipel DF) on Spodoptera littoralis larvae

Abstract: Effectiveness of commercial formulations of Bacillus thuringiensis var Kurstaki "Agerin, Dipel 2X and Dipel DF" on total protein and lipid contents were studied. Activities of detoxification and metabolic enzymes were also measured in treated and control larvae of cotton leafworm Spodoptera littoralis. Collected samples from treated larvae at intervals of 48 and 120 hrs post treatment were analyzed to assess the total protein and lipid contents as well as the enzymes activities. Significant reductions were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
3
8
0
1
Order By: Relevance
“…The results either of S. marcescens or Teflubenzuron were in agreement with those reported by Tolba (2006) when A. ipsilon pupae were treated either with S. marcescens or Flufenoxuron. On the other hand, the decreased activity in acid phosphatase due to B. thureinginsis treatment is similar to Kamel et al (2010) who found decrease in acid phosphatase activity of S. littoralis larvae after 48hrs post-treatment with B. thureinginsis commercial formulations (Agerin, Dipel 2x and Dipel DF ), whereas , it was increased after 120 hrs. for Agerin.…”
Section: Effects On Alkaline Phosphatase Activitysupporting
confidence: 87%
“…The results either of S. marcescens or Teflubenzuron were in agreement with those reported by Tolba (2006) when A. ipsilon pupae were treated either with S. marcescens or Flufenoxuron. On the other hand, the decreased activity in acid phosphatase due to B. thureinginsis treatment is similar to Kamel et al (2010) who found decrease in acid phosphatase activity of S. littoralis larvae after 48hrs post-treatment with B. thureinginsis commercial formulations (Agerin, Dipel 2x and Dipel DF ), whereas , it was increased after 120 hrs. for Agerin.…”
Section: Effects On Alkaline Phosphatase Activitysupporting
confidence: 87%
“…In addition, the decrease in total soluble protein might be due to the breakdown of protein into amino acids, so with the entrance of these amino acids to TCA cycle as keto acids, they will lead to supply energy for the insect. So, protein depletion in tissues may cause physiological mechanisms and might play a role in compensatory mechanisms under insecticidal stress, to provide intermediates to the Krebs cycle, by keeping free amino acids content in haemolymph (Nath et al, 1997 andKamel et al, 2010).…”
Section: Forms Of Malformations Induced By Camphor Oil Treatmentmentioning
confidence: 99%
“…kurstaki caused a significant reduction in the protein content of S.littoralis larvae. Kamel et al (2010) observed significant reduction in total protein content of S. littoralis larvae after treatment with B. thuringiensis var. kurstaki.…”
Section: Effects On Total Soluble Protein Contentmentioning
confidence: 83%